2021
DOI: 10.1109/access.2021.3055619
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Dependent Event-Triggered Fault Detection for Nonlinear Semi-Markov Jump Systems With Quantization: Application to Robotic Manipulator

Abstract: This paper is studied with fault detection issue for nonlinear semi-Markov jump systems. In particular, the mode-dependent mechanism of event-triggered transmission is developed for improving communication efficiency. Furthermore, the mode-dependent quantization method is utilized to cope with the limited network bandwidth. These strategies are chosen for more effective utilization of system mode information with less conservatism. Mode-dependent filter type fault detectors are constructed and sufficient condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Since the systems consisted of multiple subsystems which can be modeled via the mode jump approach, it has been widely applied for many practical scenarios such as electronics systems, 1,2 biological systems, 3,4 and robotic systems. [5][6][7] Generally, the sojourn times are deemed to comply with the exponential distribution in MJSs, and the corresponding transition rates are constants. However, some studies have shown that the transition rates of certain physical MJSs are time-varying, which means that the control design method for MJSs could be conservative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the systems consisted of multiple subsystems which can be modeled via the mode jump approach, it has been widely applied for many practical scenarios such as electronics systems, 1,2 biological systems, 3,4 and robotic systems. [5][6][7] Generally, the sojourn times are deemed to comply with the exponential distribution in MJSs, and the corresponding transition rates are constants. However, some studies have shown that the transition rates of certain physical MJSs are time-varying, which means that the control design method for MJSs could be conservative.…”
Section: Introductionmentioning
confidence: 99%
“…As a particular type among hybrid systems, numerous effects have been denoted to Markov jump systems (MJSs) owing to the significant ability to characterize the systems with sudden structure or parameter variations governed by Markov chains. Since the systems consisted of multiple subsystems which can be modeled via the mode jump approach, it has been widely applied for many practical scenarios such as electronics systems, 1,2 biological systems, 3,4 and robotic systems 5‐7 . Generally, the sojourn times are deemed to comply with the exponential distribution in MJSs, and the corresponding transition rates are constants.…”
Section: Introductionmentioning
confidence: 99%